2021
DOI: 10.3390/polym13020255
|View full text |Cite
|
Sign up to set email alerts
|

Functionalization of an Alginate-Based Material by Oxidation and Reductive Amination

Abstract: This research focused on the synthesis of a functional alginate-based material via chemical modification processes with two steps: oxidation and reductive amination. In previous alginate functionalization with a target molecule such as cysteine, the starting material was purified and characterized by UV-Vis, 1H-NMR and HSQC. Additionally, the application of FT-IR techniques during each step of alginate functionalization was very useful, since new bands and spiked signals around the pyranose ring (1200–1000 cm−… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
29
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(35 citation statements)
references
References 75 publications
4
29
1
1
Order By: Relevance
“…7). The significant difference in the chemical shifts of carbon atoms in the current study and the previous reports on the NMR of alginate did not appear because the differences were lower than 0.05 ppm [25], describled by Hans et al (1977) [26] and Peter (1988) [27]. The absorbance of the British standard solution (1mg/ml) is D=0.473.…”
Section: Physico-chemistry Characteristics Of Antioxidant Alginatecontrasting
confidence: 55%
“…7). The significant difference in the chemical shifts of carbon atoms in the current study and the previous reports on the NMR of alginate did not appear because the differences were lower than 0.05 ppm [25], describled by Hans et al (1977) [26] and Peter (1988) [27]. The absorbance of the British standard solution (1mg/ml) is D=0.473.…”
Section: Physico-chemistry Characteristics Of Antioxidant Alginatecontrasting
confidence: 55%
“…This signal disappeared in sample SAHA-60 due to a minor amount of alginate; peaks at δ 3.81, 3.80, and 3.7 ppm ascribed to the hydrogen atoms linked to the C-2, C-3, and C-4 carbons of the M residue. The alginate calcium/hydroxyapatite showed some additional characteristic peaks appearing at a range of δ 0.83-2.3 ppm, indicating that the alginate polymer microstructure was strongly dependent on the crosslinking calcium ion and the atoms of the hydroxyapatite structure [23][24][25].…”
Section: Nuclear Magnetic Resonance (Nmr)mentioning
confidence: 99%
“…A small increment of the absorption between 2900 and 3000 cm À1 , and the increased CdH stretch of the methyl group of IEM indicates functionalization [24]. Similar studies that reported the use of IR in confirming functionalization include alginate [25], methoxylated pectin and amidated LMP [13], chitosan functionalization with the PNIPAAm [26], cellulosepropargylated chitosan [27], Melamine-Functionalized Chitosan: [28], etc.…”
Section: Uv-vis Region Spectra Of the Bacterial Cellulose Samples Wit...mentioning
confidence: 54%
“…On the other hand, HSQC ( 1 Hd 13 C) can also be used to study the interaction between hydrogen and carbon atoms within a biopolymer. Huamani-Palomino et al utilized the HSQC spectrum to confirm the purification process of alginate (Figure 9B) by observing the coupling bands of the alginate monomers (glucoronic acid and mannuronic acid) [25]. Representative 1H-NMR spectra of hydrogels (a) with higher water content 1q, 2 t and (b) lower water content 3d, 4d, recorded over time (from up to down: 1, 7, 15, and 22 days) [40].…”
Section: Ft-ir Spectra Of (A) Chitin (B) Chitosan (C) Chitosan Np (D)...mentioning
confidence: 99%